Gibberellin Signaling in Plants – The Extended Version - Schwechheimer, Claus (Frontiers in Plant Science, 2012)
The plant hormone gibberellin (GA) controls major aspects of plant growth such as germination, elongation growth, flower development, and flowering time. In recent years, a number of studies have revealed less apparent roles for GA in a surprisingly broad set of developmental as well as cell biological processes. The identification of GA receptor proteins on the one end of the signaling cascade, DELLA proteins as central repressors of the pathway and transcription regulators such as the phytochrome interacting factors and the GATA-type transcription factors GNC and CGA1/GNL on the current other end of the signaling cascade have extended our knowledge about how GA and DELLAs regulate a diverse set of plant responses.